A Conversation about the Contract and Commercial Law Act 2017 - McLauchlan, David (Victoria University of Wellington Law Review, 2019)
The Contract and Commercial Law Act 2017 is the first piece of legislation prepared pursuant to the revision powers contained in the Legislation Act 2012 which allow, inter alia, for several Acts to be combined and reworded in accordance with modern language and drafting style. This article, which is written in the form of a conversation between a law student and her contract professor, seeks to evaluate the Act. The tenor of the conversation is that the Act has failed to achieve its primary purpose of making the law more accessible.